Copper and the Chilean Economy, 1960-98 - Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 1999)
The paper concludes that world copper prices play an important role in short-term fluctuations and probably influence long-term growth of the Chilean economy. While many mechanisms may be at work, investment seems to play a major role. In a copper price boom, the higher copper price and associated capital inflows create upward pressure on the real exchange rate. The appreciation of the Chilean peso during the first part of the copper cycle contributes to lower inflation, which could partly explain why real wages grow more rapidly in this part of the cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet